ANALISA PERHITUNGAN PENDAPATAN DAN PENGELUARAN DI RESTORAN DOMO GRILL AND DIMSUM GAYUNGAN SURABAYA - Jumani; Soesilawati Atmadja; Harjanti, Wulandari (Ekomania, 2023)
Restaurant is a general term that is often used to describe a business that serves food to the public and provides a place to enjoy food and set certain rates for food and service. In urban areas, there are many strategic areas to serve as restaurants. Income is an element that must be done in doing a business because in doing a business, of course, you want to know the value. the amount of income earned while doing business. income is very influential For the continuity of a business, the greater the income obtained, the greater the ability of a business to finance all expenses and activities to be carried out. A person's condition can be measured using the concept of income which shows the total amount of money that a person receives. For a certain period of time (Samuelson and Nordhaus 2013) there is another definition of income, namely income is said to be the amount of income earned from work and usually a person's income is calculated every year or every month. add fixed assets.